Can the state be held accountable for water pollution? a critical analysis of legal alternatives available to prospective litigants - Bond-Smith, Marguerite (Centre for Law and Society, 2026)
Water is considered to be one of the most essential of all natural resources 1 and its importance in the perpetuation of life is incontrovertible. The 'human poverty index' formulated by the United Nations Development Programme, lists a decent standard of living as one of the three essentials for human life, which in turn is determined by, amongst other, access to safe water. Water is one of the key resources determining the health and wealth of a nation resulting in management of the resource to ensure sustainable use being 'vital'.2 The United Nations Committee on Economic, Social and Cultural Rights significantly links the right to water, as a limited natural resource, the enjoyment of health and other human rights by stating that the right to water is indispensable to leading a life in human dignity and is a prerequisite for the realization of other human rights.